Kontribusi Sosial Pertukaran Mahasiswa Merdeka Inbound Universitas Mataram Angkatan 4 Tentang Penyuluhan Kesehatan dan Kebersihan Lingkungan di Gili Belek Lombok Timur - Hasbi, Nurmi (Jurnal Pengabdian Magister Pendidikan IPA, 2024)
Social contribution is the sixteenth activity in the entire series of inbound student exchange activities at Mataram University group 13. Social contribution aims to give students experience to chat with students and solve problems in the area. Social contributions are carried out in Gili Belek, East Lombok Regency, West Nusa Tenggara Province. Social contributions were carried out by 1 Indonesian module lecturer, 1 liaison officer and 23 students. Social contribution activities consist of two activities, namely health education and environmental cleanliness education. The target of social contribution activities is children from early childhood to elementary school in the area. The health education activity began with the team explaining how to maintain personal hygiene, such as bathing twice a day, not using the same towel as other people, washing hands before and after activities and using hand sanitizer. Outreach activities related to efforts to maintain environmental cleanliness are carried out by providing material related to sorting types of organic and inorganic waste, and habits of disposing of waste in its proper place. Social contribution activities are also provided with interesting educational games that impart knowledge to children in the environment. The service team also provided souvenirs to participants in the form of drawing books, drawing pencils, hand sanitizer toothbrushes and six trash cans. Participants participated in this social contribution with enthusiasm and joy. It is hoped that this activity can instill a sense of concern for other independent campus students and a sense of concern for the environment, especially society.